Future time orientation, life projects, and career self-efficacy of unemployed individuals - Silva, Ana Daniela; Carvalho, Catarina Luzia de; Coscioni, Vinicius; Taveira, Maria do Céu (Frontiers in Psychology, 2023)
This study examined the relationship between two variables of the psychological future [future time orientation (FTO) and life project (LP)] and their relationship with career self-efficacy in unemployed individuals. Participants were 216 unemployed adults (151 women, 65 men), aged from 18 to 67 years old (M = 42.8, SD = 10.57), who responded to measures of distance and impact of future time orientation, identification and involvement in life project and career exploration and decision-making self-efficacy. Results of latent mediation analysis and correlational analysis indicated that there is a direct effect between FTO and LP, but also an indirect (i.e. mediating) effect between them through career self-efficacy beliefs. These findings suggest that unemployed individuals with a stronger sense of future time orientation are more likely to identify and engage with their life projects, and that this organization of their life projects is mediated by their levels of career self-efficacy. Overall, the study provides important insights into the psychological factors that can impact the careers behaviors of unemployed individuals, as well as on the characteristics of career psychological interventions with this public.